2008
DOI: 10.1177/159101990801400303
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Middle Cerebral Artery Aneurysms

Abstract: The endovascular approach is described in 113 middle cerebral artery (MCA) aneurysms. The treatment failed in six cases with no adverse clinical consequences. Out of the 107 treated cases, it was possible to obtain a complete occlusion in 50 aneurysms (47%), whereas a residual aneurysm neck was observed in 54 cases (50%). Follow-up angiograms were performed in 60 cases, showing a 22% rate of further thrombosis of the aneurysm. Recanalization of the aneurysm was observed in 8% of cases, which required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…They also observed significantly lower mortality rates at five years after coiling versus surgery 10). Although endovascular treatment of MCA aneurysm has recently become popular with improved techniques and materials, the clinical and angiographic outcomes of coiling of MCA aneurysms have not outweighed clipping for treatment of MCA aneurysms until recently 2)5-6)14)19-20). MCA aneurysms are easily accessible by various surgical approaches, and their configuration is usually not suitable for endovascular treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also observed significantly lower mortality rates at five years after coiling versus surgery 10). Although endovascular treatment of MCA aneurysm has recently become popular with improved techniques and materials, the clinical and angiographic outcomes of coiling of MCA aneurysms have not outweighed clipping for treatment of MCA aneurysms until recently 2)5-6)14)19-20). MCA aneurysms are easily accessible by various surgical approaches, and their configuration is usually not suitable for endovascular treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the data from the ISUIA indicate no significant difference in adverse outcomes between clipping and coiling, although endovascular coiling yields a higher rate of recanalization. Even though many studies have reported favorable outcomes following treatment of UIAs, there seems to be bias based on the treating physician: Surgery is preferred by neurosurgeons, and endovascular treatment is usually promoted by neuro-interventionists 2)5-7)11)13-16)19-20)…”
Section: Introductionmentioning
confidence: 99%
“…In addition, van Dijk et al 21) reported a complete occlusion rate of 89% in 107 surgically treated aneurysms. The complete obliteration rate of MCA aneurysms treated endovascularly reportedly varied from 26.3% to 67% and outcomes were not better than surgical outcomes 2 7 11 16 20) . EVT has a higher rate of remnant necks than surgery due to the specific configurations of MCA aneurysms, which are characterized by a small dome-to-neck ratio, a relatively wide neck, and the possibility that one of the branches might be incorporated in the aneurysm's neck.…”
Section: Discussionmentioning
confidence: 98%
“…Aneurysm recanalization develops more frequently with endovascular coil embolization than with microsurgical treatment because of the high frequency of remnant neck and coil compaction and/or loosening 3 13) . After complete aneurysm coiling, the recanalization rate was reportedly between 8% and 27.2% 4 7 16 20 22) . Choi et al 4) announced that the overall recanalization rate of aneurysms regardless of location was 26.4% (24 of 91 aneurysms), whereas that of the MCA bifurcation, the most common site, was 75% (three of four aneurysms).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation